SIRT6-PARP1 is involved in HMGB1 polyADP-ribosylation and acetylation and promotes chemotherapy-induced autophagy in leukemia. Issue 4 (2nd April 2020) - Kong, Qian; Li, Yunyao; Liang, Qixiang; Xie, Jianwei; Li, Xinyu; Fang, Jianpei
ABSTRACT: High mobility group box protein 1 (HMGB1) is an evolutionarily conserved non-histone chromatin-binding protein. In a previous study, we showed that treating leukemic cells with chemotherapeutic drugs leads to the translocation of HMGB1, which is involved in autophagy and ultimately promotes chemoresistance in leukemia. However, the underlying translocation mechanism of HMGB1 in chemotherapy-induced autophagy remains unclear. In this study, we showed that knockdown of SIRT6 or PARP1 gene expression significantly inhibited HMGB1 cytoplasmic translocation and autophagy. Meanwhile, we found that SIRT6, an important upstream protein of PARP1, associated with PARP1, leading to the stimulation of polyADP-ribose polymerase activity. We further demonstrated that SIRT6 and PARP1 activation were required for chemotherapy-induced ADP-ribosylation of HMGB1 in leukemic cells and then influenced the acetylation of HMGB1, finally promoting the autophagy of leukemic cells mediated by HMGB1 translocation. These findings provide new insights into the mechanism of chemotherapeutic drug resistance. Targeting the HMGB1 translocation may overcome autophagy-related chemoresistance in leukemia.